Development of Teaching Performance Evaluation Application for Lecturers Using K-Nearest Neighbor Method with Manhattan Distance Approach - Helmina, Annisa; Dedy Irfan; Fahmi Rizal; Kasmita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Based on the initial observation, there are several underlying issues that form the basis of this research. The teaching performance evaluation at Padang State University has limitations regarding the courses to be evaluated. Each student can only evaluate 5 (five) courses per semester, where these five courses are randomly selected by the system, allowing each student to evaluate different courses even in the same class. The evaluation of teaching performance at Padang State University is not specific to individual lecturers but to the courses. One course can be taught by several lecturers, so students evaluating the learning cannot provide assessments for each lecturer. This results in each lecturer not having their own performance results. Furthermore, the teaching performance evaluation at Padang State University does not have a classification for the filled evaluations, thus requiring a long time to calculate the final results. This study uses the Research and Development (R&D) method with the 4-D development model consisting of four stages: definition, design, development, and dissemination. The type of data used is primary data obtained from 3 media validators, the evaluation administration of Padang State University, and 46 students. The data analysis technique used is descriptive data analysis to describe the validity and practicality of the developed lecturer performance evaluation application. The results of this development study produced a lecturer performance evaluation with 202 training data, 47 test data, resulting in an accurate system with a precision value of 88.76%, a recall value of 89.93%, and a program accuracy value of 94.04%. The validity results of the web-based learning evaluation conducted by media experts obtained a score of 0.864 with a valid category. The practicality value of using web-based lecturer performance evaluation by students obtained a score of 87.42 with a practical category. Meanwhile, the practicality value obtained by the evaluation administration of Padang State University is 89.33 with a practical category.